1998
DOI: 10.1074/jbc.273.13.7358
|View full text |Cite
|
Sign up to set email alerts
|

The Role of DnaJ-like Proteins in Glucocorticoid Receptor·hsp90 Heterocomplex Assembly by the Reconstituted hsp90·p60·hsp70 Foldosome Complex

Abstract: The glucocorticoid receptor (GR) is recovered from hormone-free cells in a heterocomplex with the molecular chaperone hsp90, which is required to produce the proper folding state for steroid binding. GR⅐hsp90 heterocomplexes are formed by a multiprotein system that appears to exist in all eukaryotic cells. Recently, we have reconstituted a receptor⅐hsp90 heterocomplex assembly system with purified rabbit hsp90 and hsp70 and bacterially expressed human p23 and p60. We have shown that hsp90, p60, and hsp70 form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
147
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 50 publications
3
147
0
Order By: Relevance
“…Pharmacological and antisense-RNA studies confirmed the hypothesis that MR in the hippocampus inhibits basal HPA axis activity by influencing CRH and AVP secretion from the PVN, whereas hippocampal GR acts the opposite (Dittmar et al, 1998) (Ratka et al, 1989).…”
Section: Corticosteroid Receptorssupporting
confidence: 48%
“…Pharmacological and antisense-RNA studies confirmed the hypothesis that MR in the hippocampus inhibits basal HPA axis activity by influencing CRH and AVP secretion from the PVN, whereas hippocampal GR acts the opposite (Dittmar et al, 1998) (Ratka et al, 1989).…”
Section: Corticosteroid Receptorssupporting
confidence: 48%
“…Toward this end, Pratt and co-workers (24,25) have successfully used purified rabbit hsp70 and hsp90 plus recombinant Hop and p23 to assemble complexes of the glucocorticoid receptor. More recently, they have also shown a requirement for hsp40 (DnaJ homolog) in this system (26). Their results indicate that glucocorticoid receptor complexes capable of binding hormone can be assembled using only hsp70, hsp40, hsp90, and Hop and that p23 is not essential but it stabilizes the receptor complexes to dramatically enhance hormone binding activity.…”
mentioning
confidence: 92%
“…Human p23 was purified from 10 ml of bacterial lysate by chromatography on DE52 followed by hydroxyapatite chromatography as described (29). For purification of YDJ-1, bacterial sonicates were cleared by centrifugation, and YDJ-1 was purified by sequential chromatography on DE52 and hydroxyapatite as described previously (14). The bacterial expression of YDJ-1 has been described (30) as has the expression of human Hop (13).…”
Section: Assay Of Steroid Binding Capacity-immunementioning
confidence: 99%
“…Hop does not act solely as a tie rod to bring the essential chaperones together; it also influences the conformational state and function of each protein (18). The hsp90⅐Hop⅐hsp70 complexes also contain small amounts of the hsp70 co-chaperone hsp40 (14), and together they form the hsp90/hsp70-based chaperone machinery. Once the machinery has assembled the GR⅐hsp90 heterocomplex, p23 binds dynamically (19) to the ATP-dependent conformation of hsp90 (20) and stabilizes its association with the receptor.…”
mentioning
confidence: 99%
See 1 more Smart Citation